Răspuns :
a+60=b
a-b=60
(a+b):(a-b)=25 rest 24
(a+b)=25(a-b)+24
(a+b)=25x60+24
(a+b)=1500+24
(a+b)=1524
(a-b)=60
adunam cele doua ecuatii si rezulta:
2a=1524+60
2a=1584
a=1584:2
a=792
b=792-60
b=732
a-b=60
(a+b):(a-b)=25 rest 24
(a+b)=25(a-b)+24
(a+b)=25x60+24
(a+b)=1500+24
(a+b)=1524
(a-b)=60
adunam cele doua ecuatii si rezulta:
2a=1524+60
2a=1584
a=1584:2
a=792
b=792-60
b=732
a=b+60
(a+b):(a-b)=25r24=>a+b=25(a-b)+24
b+60+b=25(b+60-b)+24=>2b+60=25b+1500-25b+24=>2b=1500+24-60=>
b=1464:2=>b=732
a=732+60=>a=792
(a+b):(a-b)=25r24=>a+b=25(a-b)+24
b+60+b=25(b+60-b)+24=>2b+60=25b+1500-25b+24=>2b=1500+24-60=>
b=1464:2=>b=732
a=732+60=>a=792